Il progetto della conoscenza nell’ambito del restauro della grotta degli Animali a Castello. Significato e ruolo di indagini, studi, diagnostica - Scelza, Hosea (Opus Incertum, 2019)
The restoration of the Grotta degli Animali in the garden of the Medicean Villa of Castello is an ongoing project promoted by the Polo Museale per la Toscana in collaboration with the Soprintendenza A.B.A.P. of Florence, both regional offices of Italy’s Ministry of Cultural Heritage. The text displays the multidisciplinary approach set up in order to gain further knowledge of the monument and, consequently, to be able to develop the most appropriate conservation actions. The multidisciplinary activities concern various aspects: from diagnostics to survey, from the specification of the monument’s material structure to the study of archival records. The data collected is made available to the technical staff supervising the works in order to critically discuss scientific results and steer their choices based on factual information. “Critically” is a keyword here, since scientific data does not set rules for architects and art historians regarding how restoration must be conducted, but stands as a tool for accurate operational measures.